Linking adolescents’ phubbing to depression: the serial mediating effects of peer relationship quality and psychological need frustration - Yue, Heng; Gao, Shiwen; Feng, Fei; Wu, Feiteng; Bao, Hugejiletu; Zhang, Xuemin (Frontiers in Public Health, 2024)
IntroductionPhubbing is defined as a phenomenon in which individuals use their smartphones during conversations with others, focusing on the smartphones and escaping from interpersonal interactions. This phenomenon has been extensively studied in the literature. However, most studies concerning phubbing have focused on understanding its impact on the receivers; few have investigated the consequences of phubbing on the actors themselves. The present study aimed to explore the link between adolescents’ phubbing behavior and depression, focusing on the underlying psychological mechanisms.MethodsA total of 441 Chinese high school students participated in this study in September 2023. SPSS 25.0 and AMOS 24.0 were used to analyze the data. A hierarchical linear regression analysis was used to test the effect of phubbing on depression. A serial mediation model was applied to assess the roles of peer relationship quality and psychological need frustration in the link between phubbing and depression.ResultsThis study found that among adolescents, (1) phubbing had a significant direct association with depression; (2) phubbing had two significant indirect associations with depression, separately mediated via peer relationship quality and psychological need frustration; (3) the direct effect of phubbing on depression was sequentially mediated through peer relationship quality and psychological need frustration; (4) these results were applicable to both male and female adolescents.DiscussionThese findings suggested that interventions aimed at improving peer relationships and addressing psychological need frustration might reduce depressive symptoms associated with phubbing in adolescents.